Mustahik Shift Strategy in Forming Muzakki Through an Independent Family Program at The Al Falah Social Fund Foundation in Jember - Mohammad Ilham; Moch. Chotib; Nurul Widyawati IR (Cita konsultindo, 2024)
The Muslim population of Jember Regency has considerable potential in terms of zakat regulation. This is illustrated in a study of the